2021
DOI: 10.3390/plants10020194
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Mechanisms of the Aromatic and Medicinal Plant Salvia sclarea L. to Excess Zinc

Abstract: In recent years, due to the development of industrial and agricultural production, heavy metal contamination has attracted increasing attention. Aromatic and medicinal plant Salvia sclarea L. (clary sage) is classified to zinc (Zn) accumulators and considered as a potential plant for the phytoremediation of heavy metal polluted soils. In this study, an adaptation of clary sage to 900 µM (excess) Zn exposure for eight days in a hydroponic culture was investigated. The tolerance mechanisms under excess Zn exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 78 publications
0
42
0
Order By: Relevance
“…Zinc (Zn 2+ ) belongs to a group of eight essential micronutrients that are required for normal plant growth, development, and defense [9,10]. Zinc is involved in various metabolic processes, playing catalytic, regulatory, and structural roles with several crucial functions in the cell [9][10][11][12][13][14][15][16]. It performs a fundamental role in anti-oxidative defense and retains the membranous structure of various cell organelles [14,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc (Zn 2+ ) belongs to a group of eight essential micronutrients that are required for normal plant growth, development, and defense [9,10]. Zinc is involved in various metabolic processes, playing catalytic, regulatory, and structural roles with several crucial functions in the cell [9][10][11][12][13][14][15][16]. It performs a fundamental role in anti-oxidative defense and retains the membranous structure of various cell organelles [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is involved in various metabolic processes, playing catalytic, regulatory, and structural roles with several crucial functions in the cell [9][10][11][12][13][14][15][16]. It performs a fundamental role in anti-oxidative defense and retains the membranous structure of various cell organelles [14,17]. Zn 2+ deficiency or Zn 2+ at high concentration in the soil, which occurs in various habitats, ranging from deficient to toxic levels can cause inhibition of numerous plant metabolic processes, reduce plant growth and photosynthesis, and decrease chlorophyll content in the leaf, provoking chlorosis and leaf necrosis [9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, recent studies reported anti‐inflammatory, antimicrobial and analgesic, as well as antidiabetic and cytotoxic effects 2 . In addition to biological activities, S. sclarea is one of the most economically important plants for phytoextraction and phytostabilization of zinc and cadmium contaminated soils, 28,29 and because of this, there is growing interest in cultivation of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…For statistical analysis, chlorophyll fluorescence measurements are introduced as the mean ± SD. Paired t -tests at a level of p < 0.05 were performed with the StatView software (computer package, Abacus Concepts, Inc., Berkley, CA, USA) as before [ 11 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%